Al-Fatani's Perspectives on Islamic Family Law: Insights from Hidayah Al-Muta’allim Wa’Umdah Al-Muta’alim - Ahmad Sharifuddin Mustapha; Nur Zainatul Nadra Zainol; Che Adenan Mohammad; Mustapahayuddin Abdul Khalim; Nik Kamal Wan Muhammed; Muhamad Syazwan Faid (Journal of Islamic Thought and Civilization, 2024)
The evolution of Islamic Family Law in Malaysia is a nuanced amalgamation of Malay customs, cultural influences, and Islamic jurisprudence. Rooted in the history of Malaya, the formation of current Islamic Family Law reflects the fusion of these elements. This study delves into  Daud Abdullah Al-Fatani's seminal work Hidayah Al-Muta’allim Wa’Umdah Al-Muta’alim, a pivotal contribution to Malaysian Islamic jurisprudence. Comparing Al-Fatani's insights with those of scholars from diverse schools of thought and contemporary Islamic Family Law enactments, the focus remains on key issues such as Zihār, Khiyar, and Nusyuz. The study reveals that Al-Fatani's perspectives transcend strict adherence to the Al-Shafi‘i school, while aligning with the Islamic Family Law (Federal Territories) Act 1984. His views on marriage dissolution and wife’s disobedience are influenced by Malay culture, while maintaining fidelity to the Qur’ān and Sunnah exemplified by his stance on Zihār. This resonates in Malaysia's current Islamic Family Law which is not rigidly bound to the Al-Shafi‘i school but intricately considers cultural conditions.